The effect of counseling on menstrual personal hygiene knowledge in grade VII female students - Meilaningsi Meilaningsi; Siti Arifah; Triani Rahmadewi (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Early adolescence is a transitional period that is vulnerable to various reproductive health problems, particularly due to a lack of understanding of personal hygieneduring menstruation. Insufficient knowledge among adolescent girls about maintaining reproductive organ hygiene can increase the risk of infection and lead to physical and psychological impacts. Purpose: to determine the effect of health education on menstrual personal hygieneknowledge among seventh-grade female. Method: This study employed a quantitative approach, employing a pre-experimental method with a one-group pretest-posttest design and no comparison group. This means that all variables were collected simultaneously to assess the effect of counseling on personal hygiene knowledge among seventh-grade female students at SMPN 2 Mlati. The independent variable in this study was counselling. Results: The results of data analysis using the Wilcoxon test showed a significance value of p = 0.000< 0.05, which means that there is an effect of health education on menstrual personal hygiene knowledge before and after the education among seventh-grade female students. Conclusion: There is an effect of health education on menstrual personal hygiene knowledge among seventh-grade female students. Based on the results of this study, schools and health workers are expected to provide reproductive health education regularly and provide supporting facilities so that female students can practice good personal hygieneduring menstruation. Suggestion: Based on the results of this study, schools and health workers are expected to provide reproductive health education regularly and provide supporting facilities so that female students can practice good personal hygieneduring menstruation.